Nature in György Lukács and Alfred Schmidt: Marxist reflections on the beginning of the Anthropocene - van der Laan, Murillo (Argumentum, 2024)
This paper critically contrasts György Lukács’ and Alfred Schmidt’s 1960s interpretations of Marxist reflections on nature. It argues that Schmidt’s position on nature produces a literal constructivism that Lukács’ ontological perspective avoids. It also argues that Lukács generalises Marx’s theory of value in a way that hinders the historical analyses of different social metabolisms, in contrast to Schmidt’s more historicised interpretation of value, which draws out important considerations regarding capitalism’s relationship with nature. It further argues that both positions, in analysing the Marxist perspective of an emancipated society, not only depart from Marx’s positions but also fall into what environmental sociology has termed exemptionalism. Finally, it demonstrates how the theorising of István Mészáros and the so-called Metabolic Rift School skilfully reframe the positive aspects and limitations of Schmidt and Lukács’ interpretations.